Quantifying the Impact of Technical Barriers to Trade : A Framework for Analysis - Maskus, Keith E.; Wilson, John S.; Otsuki, Tsunehiro (World Bank, Washington, DC, 2014)
There has been increasing use of technical regulations as instruments of commercial policy in the context of multilateral, regional, and global trade. These nontariff barriers are of special concern to developing countries, which may bear additional costs in meeting mandatory standards. Many industrial and developing countries express frustration with regulations that vary across their export markets, require duplicative conformity procedures, and are continually revised to exclude imports. The authors provide a comprehensive overview of the policy debate and methodological issues surrounding product standards and technical barriers to trade. They begin with a review of the policy context driving demand for empirical analysis of standards in trade, then provide an analytical overview of the role of standards and their relationship to trade. They then review methodological approaches that have been used to analyze standards and their impact on trade. Their main interest lies in advancing techniques that are practical and may be fruitfully extended to the empirical analysis of regulations and trade. They discuss concrete steps that could be taken to move forward a practical, policy-relevant program of empirical research. Such steps would include: a) administering firm-level surveys in developing countries; b) devising methods for assessing how much standards restrict trade; and c) establishing econometric approaches that could be applied to survey and microeconomic data, to improve understanding of the role of standards in exports.